Advance in Topology and Functional Analysis — In Honour of María Jesús Chasco’s 65th Birthday (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The interaction between topology and functional analysis has been a wellspring of powerful mathematical ideas and developments since the early stages of both disciplines. It is obvious that many classical theorems from functional analysis have a strong topological flavour. In the other direction, probably the best-known example is the way abstract harmonic analysis informs many essential features of locally compact groups and Pontryagin duality. This influence is also exerted through many tools and concepts from the theory of topological vector spaces that have been either generalized to topological abelian groups or adopted as templates to study their structure and duality properties beyond the locally compact case. Besides topological groups, this Special Issue also contains papers on fuzzy groups, semigroups, topological vector spaces and real analysis. Their authors are well-known specialists and the different viewpoints provided by them will surely inspire future research on these exciting topics. This Special Issue pays tribute to María Jesús Chasco's mathematical career on the occasion of her 65th birthday.